Addressing Challenges and Development in Enforcing International Laws on Child Soldiers: The Need for Legal Reform - Obinna Nnanna Okereke; Uche Nnawulezi; Salim Bashir Magashi; Septhian Eka Adiyatma; Kasim Balarabe (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
The purpose of this paper is to examine the challenges of enforcing the international legal framework on child soldiering. The paper reveals that, as the offense of child soldiering escalates, the multi-dimensional scope for protecting child soldiers spans various legal regimes under international law. It argues that, despite several prohibitive norms established in International Humanitarian Law (IHL), International Human Rights Law (IHRL), the International Labour Organization (ILO), and International Criminal Law (ICL), their application or enforcement against child soldiering remains ineffective and inadequate due to numerous impediments and challenges. This is because